The Role of Nitric Oxide-Induced ATILL6 in Growth and Disease Resistance in Arabidopsis thaliana - Khan, Murtaza; Al Azawi, Tiba Nazar Ibrahim; Pande, Anjali; Mun, Bong-Gyu; Lee, Da-Sol; Hussain, Adil; Lee, Byung-Hyun; Yun, Byung-Wook (Frontiers in Plant Science, 2021)
Nitric oxide (NO) is a signaling molecule that regulates various processes, including plant growth and development, immunity, and environmental interactions. Using high throughput RNA-seq data, we explored the role of the NO-induced ATILL6 gene in plant growth and defense using functional genomics. The atill6 mutant and wild-types were challenged with either oxidative (H2O2, MV) or nitro-oxidative (CySNO, GSNO) stress conditions, and the phenotypic results showed that ATILL6 gene differentially regulates cotyledon development frequency (CDF) as well as the root and shoot lengths of the plants. To investigate whether ATILL6 plays a role in plant basal or resistance (R)-gene-mediated defense, the plants were challenged with either virulent or avirulent strains of Pseudomonas syringae pathovar tomato (Pst) DC3000. The atill6 line showed a susceptible phenotype, higher pathogen growth, and highly reduced transcript accumulation of PR1 and PR2 genes. These results suggested that ATILL6 positively regulates plant basal defense. Furthermore, after the inoculation of atill6 with avirulent Pst (DC3000), the expressions of the PR1 and PR2 genes decreased, suggesting a positive role in R-gene-mediated resistance in protecting the plant from further spread of disease. We also investigated the role of ATILL6 in systemic acquired resistance (SAR), and the results showed that ATILL6 positively regulates SAR, as the mutant line atill6 has significantly (p ≤ 0.05) lower transcript accumulation of PR, G3DPH, and AZI genes. Overall, these results indicate that the NO-induced ATILL6 gene differentially regulates plant growth and positively regulates plant basal defense, R-gene-mediated resistance, and SAR.